PNA-Modified Liposomes Improve the Delivery Efficacy of CAPIRI for the Synergistic Treatment of Colorectal Cancer - Diao, Wenbin; Yang, Ben; Sun, Sipeng; Wang, Anping; Kou, Rongguan; Ge, Qianyun; Shi, Mengqi; Lian, Bo; Sun, Tongyi; Wu, Jingliang; Bai, Jingkun; Qu, Meihua; et al. (Frontiers in Pharmacology, 2022)
The tumor associated antigen, Mucin 1 (MUC1) was highly expressed in colorectal cancer, which positively correlated with poor patient outcomes and advanced stages at diagnosis. Irinotecan and capecitabine is a standard chemotherapy combination for metastatic colorectal cancer known as XELIRI or CAPIRI, which significantly prolonged progression free survival and overall survival of colorectal cancer patients compare to single drug alone. We previously reported that peanut agglutinin (PNA) conjugated liposomes showed enhanced drug delivery efficiency to MUC1 positive liver cancer cells. In this study, we prepared irinotecan hydrochloride (IRI) and capecitabine (CAP) co-loaded liposomes modified by peanut agglutinin (IRI/CAP-PNA-Lips) to target MUC1-positive colorectal cancer. The results showed that IRI/CAP-PNA-Lips showed enhanced targeting ability for MUC1-positive colorectal cancer cells compared to unmodified liposomes. Treatment with IRI/CAP-PNA-Lips also increased the proportion of cellular apoptosis and inhibited cell proliferation of colorectal cancer cells. The targeting specificity to tumor cells and anti-tumor effects of PNA modified liposomes were significantly increased in tumor-bearing mice with no severe cytotoxicity to normal tissues. All these results suggested that co-loaded PNA-modified liposomes may provide a new delivery strategy for the synergistic treatment of colorectal cancer with clinical chemotherapeutic agents.